No. 1 2-SON DEKABR, 2025 -YIL PROSPECTS FOR THE DEVELOPMENT OF INNOVATION ACTIVITY IN UKRAINE AND UZBEKISTAN: MODERN CHALLENGES (Marketing Journal, 2025)
In the article the authors present a hypothesis that the modern revolution in the field of innovation is associated with digitalization, which leads to the transformation of entire industries and businesses, in connection with which the characteristics of digital transformation as a process are given, the need to identify modern trends in innovation activity in the eco nomy of any country is substantiated , and the analysis of innovation activity in Ukraine and Uzbekistan made it possible to identify pattern s and № 1 243 signs of the manifestation of general trends and formulate directions for enhancing innovative development in the state.
Keywords: digitalization; digital transformation; innovation; innovative activity; fintech ecosystem; national brand